Perancangan Ruang Publik Kreatif di SMAN 1 Padalarang, Kabupaten Bandung Barat - Novis Putri, Tika; Syahriyah, Dewi Rachmaniatus; Septian , Ridho; Musyofa Maulida Nufus, Muhammad (Jurnal Pengabdian Tri Bhakti, 2024)
Based on the results of surveys and observations on the buildings and complex of SMAN 1 Padalarang, PKM implementers found various problems that had the potential to become design challenges and various other building elements that did not meet safety standards as an earthquake response school. The results of observations and interviews with the Principal also show that there is a problem with open space that is less representative, especially in the area near the entrance. Apart from that, problems were also found in the main open space, namely the sports field area, related to the condition of the existing stands which did not meet the comfort and safety standards of the stands. With the background of these issues and problems, Community Service activities were carried out in the form of Creative Public Space Design at SMAN 1 Padalarang, West Bandung Regency. The output of this PKM activity is in the form of a creative public space design document at SMAN 1 Padalarang. It is hoped that the results of the school's creative public space design can be applied in other schools as school facilities that support student activities and are safe and apply disaster response principles in the school environment.